Mad Wives and Island Dreams Shimao Toshio and the Margins of Japanese Literature - Gabriel, Philip (University of Hawaii Press, 1998)
Hailed by the noted critic Karatani Kojin as a more important and lasting writer than Mishima, Shimao Toshio (1917-1986) remains almost unknown in the West. Several of his short stories have appeared in English translation, yet it is only now, with the publication of Philip Gabriel's comprehensive and searching study, that Shimao's work is being introduced to the worldwide audience it deserves. Mad Wives and Island Dreams not only is a thorough assessment of the literary legacy of a highly original and influential writer, but also represents a significant contribution to the consideration of much broader issues relating to the emergence and nature of the postwar Japanese sense of identity. Shimao's fiction covers a wide range of topics: the war and its aftermath, the unconscious, the nuclear family, madness, the position of women, the culture of Japan's southern islands.